THE IMPROVING OF PRACTICAL EDUCATIONAL STUDIES OF LEGAL DISCIPLINES, BY QUALITY IMPLEMENTATION TECHNOLOGIES - Хом’яченко, Світлана Іванівна; Хоцяновська, Наталія Францівна; Часова, Тетяна Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the authors of the article attempt to study innovative methods of legal teaching disciplines that can help to optimize the learning process, improve its quality, and to promote the integration of theory and practice. Methods of research: in the work are dialectical method of cognition, general scientific and special methods were used. Results: it is substantiated that application of quest technologies will be supplementary traditional educational process. Discussion: finding ways to improve the quality of learning through the using of quest technologies.